(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The learning process that has been done face-to-face in class has turned into a new habit, which is done online. Education must continue to be carried out considering that Indonesian children are the hope of the nation’s future which we must prepare by learning. Information technology is one of the technologies that is growing very rapidly, even during this pandemic. SMA Negeri 1 Tanjungsari is a school located in the South Lampung area and is a superior or advanced school. However, in these schools, the lack of knowledge in the field of information technology can cause obstacles to the learning and teaching process, so it is necessary to be equipped with knowledge in the field of information technology to improve digital literacy skills and learning platforms for students in schools. In connection with the problems that have been described, this service provides a solution by holding a training and creating a learning platform based on e-learning for schools and students based on information technology. This platform was created by the team with the hope of contributing to the school as a learning centre for students. The result of this PkM program is a B-Smart application product as a learning medium for high school students and training is carried out in its operation so that it can be implemented immediately. Digital literacy skills training provides an increase in understanding in the community, seen from the pre and post tests showing an 86% increase in understanding.